Konservasi Aliran Sungai Berbasis Masyarakat Dalam Upaya Pengelolaan Sumber Daya Alam Dengan Pembangunan Desa Wisata Di Desa Padang Kedondong Kecamatan Tanjung Kemuning Kabupaten Kaur - Clareza, Yessy; Barchia, M. Faiz; Brata, Bieng; Simarmata, Marulak; Romdhon, Mustopa (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2023)
Management of watersheds (DAS) is carried out to regulate the reciprocal relationship between natural resources in the watershed and humans in order to realize ecosystem sustainability and ensure the sustainability of the benefits of these natural resources for humans. This research was conducted in Padang Kedondong Village, Tanjung Kemuning District, Kaur Regency. The village was chosen because it is located in the Padang Guci watershed which is one of the priority watersheds. This research was conducted during April-May 2021. The results of the research that has been carried out are as follows: 1. The socio-economic indicators for the Padang Guci watershed have an average value of 2.05 (from an interval of 1 = bad to 3 = good), meaning it is included in good criteria (2 < x 3), 2. The people of Padang Kedondong Village in general have knowledge and awareness of ecology. Basically, with the existence of these resources, the community wants to get better results to improve welfare and pay attention to and increase the carrying capacity of the environment. 3. Currently Padang Kedondong Village is carrying out natural resource management functions/activities which include planning (planning) which is carried out by building a village vision, identifying and mapping village potential, identifying problems that occur in the development process, organizing which is held directly by the Village Head and assisted by village youths, implementation (actuating) with active participation from the community, and controlling is carried out by the Village Head. This indicates that natural resource management activities are going well and the community is able to manage natural resources in a participatory and independent manner. 4. At this time CBNRM in Padang Kedondong Village cannot be said to be good or not because it is still in process/underway which is expected to be able to balance the goals of community empowerment and natural resource conservation in the form of equity, empowerment by giving the community authority in making decisions, conflict resolution has never happened and it is hoped that in the future there will be no conflict between the community, knowledge and awareness in this case the community is able to preserve the existing nature wisely especially in land use , as well as protection of biodiversity (biodiversity protection) the public is prohibited from taking fish with poison and electricity. Whereas in the aspect of sustainable utilization of natural resources (sustainable utilization) results have not yet been seen because it is only being developed.           Keywords: Padang Kedondong Village, tourism village, watershed conservation